EFFICIENT DONATION, SUSTAINABLE IMPACT: UNVEILING THE CLOTHES RECYCLE MANAGEMENT SYSTEM - Abdul Rahim, N. S.H.; Rahmalan, H. (Journal of Advanced Computing Technology and Application (JACTA), 2024)
This paper presents the development of the Clothes Recycle Management System (CRMS), designed to address the inefficiencies in the current methods of promoting and managing clothing donations, which rely heavily on manual processes and social media. The objective of this study is to create and implement a unified, user-friendly platform that streamlines the donation process, enhances accessibility, and improves the overall efficiency of clothing donation activities. Key features of the system include event organization, item tracking, automated reporting, and a points-based incentive scheme that encourages donations. Additionally, the system provides transparency by informing users about the destination of their donations, fostering trust and engagement. The findings demonstrate that CRMS significantly simplifies donation coordination, increases donor participation through the incentive scheme, and offers reliable data for stakeholders to assess the impact of their efforts. This study concludes that CRMS is a viable solution for enhancing sustainability and community involvement in clothing donations, with the potential for broader application in other donation-driven initiatives.